Water in the Rocky Mountain West, 2025 - Colorado Institute of Public Policy, author (Colorado State University. Libraries, 2006)
The Rocky Mountain West continually faces complicated and rapidly changing water policy challenges. Today, water issues are fundamentally about the people of the West, and the diverse beliefs and values that they hold. To illustrate how beliefs and values are connected to water challenges, this presentation accompanies report, "Water in 2025: beliefs and values as a means for cooperation" (http://hdl.handle.net/10217/577), and highlights the results of two surveys given to 84 stakeholders in Colorado.
Keywords: Water rights -- West (U.S.); Water quality -- West (U.S.); Water use -- West (U.S.); Lifestyles -- Rocky Mountains